Using secondary analysis of qualitative data of patient experiences of health care to inform health services research and policy - Ziebland, S; Hunt, K (SAGE Publications, 2014)
Qualitative research is recognized as an important method for including patients’ voices and experiences in health services research and policy-making, yet the considerable potential to analyse existing qualitative data to inform health policy and practice has been little realized. This failure may partly be explained by: a lack of awareness amongst health policy makers of the increasing wealth of qualitative data available; and around 15 years of internal debates among qualitative researchers on the strengths, limitations and validity of re-use of qualitative data. Whilst acknowledging the challenges of qualitative secondary data analysis, we argue that there is a growing imperative to be pragmatic and to undertake analysis of existing qualitative data collections where they have the potential to contribute to health policy formulation. Time pressures are inherent in the policy-making process and in many circumstances it is not possible to seek funding, conduct and analyse new qualitative studies of patients’ experiences in time to inform a specific policy. The danger then is that the patient voice, and the experiences of relatives and carers, is either excluded or included in a way that is easily dismissed as ‘unrepresentative’. We argue that secondary analysis of qualitative data collections may sometimes be an effective means to enable patient experiences to inform policy decision-making.